Pandemic induced uncertainties, challenges and threats to developing countries: A case study of Pakistan - Chishti, Mazhar; Ambreen Afzal; Madiha Afzal (Journal of Arts & Social Sciences, 2020)
The aim of this investigation is about the economic effects of Coronavirus, broadly branded as COVID-19. Since its initiation in China, it has cast-iron a large number of lives of human while living millions in isolate in view of viral diseases. Where it brings significant human affliction, it additionally makes worldwide economic interruptions around the world. It obstructs development and smooth activity of businesses of all kinds which badly hamper the balance of trade, exports, imports; public spending, remittances, capital formation process and financial markets all are in the dangers of COVID-19. The whole world goes through a similar example for example curfews and lockdown of changing degrees leaving markets and working environments dead. It stops income age as well as acquires an extraordinary expense to states while managing with worldwide pandemic in the midst of general wellbeing. Accordingly, its economies effects are all the more distressing and subverting. The economies like Pakistan which is already facing political and economic trials is in intimidating position alongside negative developments are confronting a lack of assets to battle with it not to mention bearing income misfortune.